Les architectes en coworking. Ou le renouvellement d’une figure de l’architecte - Stéphanie Dadour; Lucie Perrier (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
In 2018, the demographic and economic observatory of the architectural profession, published by the French National Council of Architects, introduced coworking as one of the main collaboration tools used by architects for the first time. Collaboration appears to be one of the ways that marks the transformations of the practice of architecture, and therefore the architect’s choice of workspace. In this article, we will focus on the relationships between the transformations of the activities of architectural agencies who practice coworking, as well as on the reasons that encourage architects to settle in coworking spaces: between being a model or an opportunity, to what extent does coworking participate in the practice of the architect? This article does not seek to trace the history or managerial aspect of agencies, but to understand what architects get from these places, in a context where the profession is undergoing legislative changes and devaluing representations — in particular the decrease in the leadership of architects on projects, as reflected in the ELAN law, for example.